2011
DOI: 10.1007/s11726-011-0511-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessments of different kinds of sham acupuncture applied in randomized controlled trials

Abstract: 【Abstract】Objective: Different kinds of sham acupuncture are widely applied in randomized controlled trials (RCTs) to explore whether acupuncture has intrinsic therapeutic effects beyond the placebo effects for certain indication. To make conclusions of trials more comparable and convincing, it is of great necessity to unify the sham acupuncture procedure. Methods: RCTs of acupuncture with high quality in the recent 14 years were reviewed, and the appropriateness of the sham acupuncture procedures was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 30 publications
0
16
1
Order By: Relevance
“…While 2 studies that included 175 patients reported VAS scores that were lower in acupuncture compared with medication at a follow-up time of 1–3 months after treatment (random-effects estimates; MD −1.81, 95%CI −3.42 to −0.20; P -value of the Chi 2 test <0.0001, I 2 = 94%; P -value of Z test = 0.03; very low quality; Figure 3A shows the results; Li, 2017 ; Shu et al, 2017 ). For acupuncture and sham acupuncture,a total of 9 trials that included 409 patients presented VAS scores were lower with acupuncture than with sham acupuncture at a follow-up time of up to 1 month after treatment (random-effects estimates; MD −1.56, 95%CI −2.21 to −0.92; P -value of the Chi 2 test <0.00001, I 2 = 82%; P -value of Z test <0.00001; low quality; Figure 3B shows the results; Chen, 2009 ; Jiang, 2011 ; Jiang et al, 2011 ; Zhao, 2011 ; Gao, 2012 ; Wan et al, 2013 ; Wu, 2014 ; Zhang, 2014 ; Wang et al, 2015 ; Liang et al, 2016 ).…”
Section: Resultsmentioning
confidence: 97%
“…While 2 studies that included 175 patients reported VAS scores that were lower in acupuncture compared with medication at a follow-up time of 1–3 months after treatment (random-effects estimates; MD −1.81, 95%CI −3.42 to −0.20; P -value of the Chi 2 test <0.0001, I 2 = 94%; P -value of Z test = 0.03; very low quality; Figure 3A shows the results; Li, 2017 ; Shu et al, 2017 ). For acupuncture and sham acupuncture,a total of 9 trials that included 409 patients presented VAS scores were lower with acupuncture than with sham acupuncture at a follow-up time of up to 1 month after treatment (random-effects estimates; MD −1.56, 95%CI −2.21 to −0.92; P -value of the Chi 2 test <0.00001, I 2 = 82%; P -value of Z test <0.00001; low quality; Figure 3B shows the results; Chen, 2009 ; Jiang, 2011 ; Jiang et al, 2011 ; Zhao, 2011 ; Gao, 2012 ; Wan et al, 2013 ; Wu, 2014 ; Zhang, 2014 ; Wang et al, 2015 ; Liang et al, 2016 ).…”
Section: Resultsmentioning
confidence: 97%
“…We will investigate following treatment comparisons: Acupuncture versus no treatment Acupuncture versus sham acupuncture 23 Acupuncture versus other treatment Acupuncture with another treatment versus the same treatment without acupuncture. …”
Section: Methods and Analysismentioning
confidence: 99%
“…Sham acupuncture includes sham acupuncture at selected acupoints, sham acupuncture at non-acupoints, needling at inappropriate acupoints, non-penetrating sham acupuncture and pseudo interventions). 24 The following treatment comparisons will be investigated.…”
Section: Methods and Analysismentioning
confidence: 99%